2020
DOI: 10.1007/s11368-020-02741-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chlorella sp. and rhamnolipid 90 in maintaining homeostasis in soil contaminated with bisphenol A

Abstract: Purpose The knowledge about the impact of BPA on soil health does not correspond to the great interest in its analogues. Therefore, a study was conducted to determine the potentially negative impact of BPA on the biochemical properties of soil. The study also evaluated the effectiveness of two biostimulants in eliminating potential homeostasis disorders caused by BPA. Materials and methods A pot experiment was conducted under supervised conditions. BPA at five contamination levels was added to the soil of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 86 publications
3
2
0
Order By: Relevance
“…The bacteria which can also cometabolize or use bisphenol A as a source of carbon proved to be Devosia , Novosphingobium and Achromobacter . The results of our observations coincide with the pools of microorganisms indicated by Zhang et al [ 79 ] and Zaborowska et al [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The bacteria which can also cometabolize or use bisphenol A as a source of carbon proved to be Devosia , Novosphingobium and Achromobacter . The results of our observations coincide with the pools of microorganisms indicated by Zhang et al [ 79 ] and Zaborowska et al [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…of soil had an inhibitory effect on the activity of acid phosphatase, urease and β -glucosidase. The current research results are comparable to the results obtained by Zaborowska et al [ 55 , 56 ] and Siczek et al [ 57 ]. The research showed a negative effect of BPA on the biochemical activity of soil.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The activity of the dehydrogenases was determined using the Lenhard method modified by Öhlinger [54], and the catalase, urease, β-glucosidase, arylsulfatase, acid phosphatase, and alkaline phosphatase activities were determined using the method of Alef and Nannipieri [55]. Enzyme activity was expressed in moles or their subunits of the produced product per 1 kg of soil in the course of 1 h. The exact assay procedures have been described in our previous publications [56,57].…”
Section: Determination Of Enzyme Activitymentioning
confidence: 99%